Ostseebad Zoppot Kurhaus, Wein-Terrasse / Photogr. J. Faltin. - Faltin, John (1846-1918) (Verlag Clara Bernthal, 1909)
Przedstawia rotundę Domu Zdrojowego (wyb. 1909 r.), w której mieściła się winiarnia, ok. 1910 r.